(untitled) (Research, Society and Development, 2024)
The aim of this research was to evaluate the performance of a central pivot irrigation system using energy from an isolated photovoltaic system, through a study experimental lab quantitative study. The energy supply consisted of eight photovoltaic modules with a power of 665W and a 1.5kW frequency inverter, finally connected directly to the pumping system. The power parameters of the photovoltaic system and the water pump motor were measured simultaneously while collecting the water flow from the central pivot. The experiment was conducted at the Experimental Center for Agricultural Engineering (NEEA) at the State University of Western Paraná, UNIOESTE, carrying out 5 days of collection with 30 tests per day, totaling 150 collections. Energy generation by the photovoltaic system was unstable with a coefficient of variation of 9.82 to 56.74%, while the pressure and flow values ​​remained within the nominal specification values ​​according to the process capacity index. The uniformity values ​​were between 54.78 and 61.38%, therefore classified as poor, however it is highlighted that the stability of energy generation improved uniformity. Shewhart’s control charts defined that the presence of clouds, as well as low radiation values, affect the energy generation, pressure and flow of the irrigation system, compromising uniformity. Therefore, it is concluded that the layout of the system under study was not satisfactory for appropriate central pivot irrigation. It is therefore recommended to use a battery bank to stabilize energy generation and consumption.